2010
DOI: 10.1097/ss.0b013e3181cb7f46
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pecan Biochar on Physical Properties of a Norfolk Loamy Sand

Abstract: Because the southeastern US Coastal Plain has high temperatures and abundant rainfall, its sandy soils have poor physical characteristics and low carbon (C) contents. To increase soil C, we added switchgrass (Panicum virgatum) and nonactivated recalcitrant pecan biochar. Biochar was developed by pyrolyzing ground pecan shells at 700 -C. Biochar had 88% C, 0.4% N (C:N ratio, 220:1); 58% of its C resided in polymerized aromatic ring structures. Biochar treatments were 0, 5, 10, or 20 g kg j1 of soil, which was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
112
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(126 citation statements)
references
References 23 publications
11
112
2
1
Order By: Relevance
“…Increase in MWD compared with control might be attributed to large organic C content of the amendments (Table 2) and could also be due to their high Ca and Mg contents (Table 2) that might help produce stronger physical bonds between particles ). Similar to our results, Busscher et al (2010) also did not observe any increase in MWD after addition of biochar in the loamy sands after 70-day incubation. Therefore, further work is needed to modify biochar T1 T2 T3 T4 T5 T6 T7 P1 T1 T2 T3 T4 T5 T6 T7 T1 T2 T3 T4 T5 T6 T7 P1 T1 T2 T3 T4 T5 T6 T7 P2 Extractable Ca (mg/kg) 500 1000 1500 2000 T1 T2 T3 T4 T5 T6 T7 P1 T1 T2 T3 T4 T5 T6 T7 P2 Extractable Mg (mg/kg) 100 200 300 400 T1 T2 T3 T4 T5 T6 T7 P1 T1 T2 T3 T4 T5 T6 T7 P2 Fig.…”
Section: Effects On Soilssupporting
confidence: 81%
“…Increase in MWD compared with control might be attributed to large organic C content of the amendments (Table 2) and could also be due to their high Ca and Mg contents (Table 2) that might help produce stronger physical bonds between particles ). Similar to our results, Busscher et al (2010) also did not observe any increase in MWD after addition of biochar in the loamy sands after 70-day incubation. Therefore, further work is needed to modify biochar T1 T2 T3 T4 T5 T6 T7 P1 T1 T2 T3 T4 T5 T6 T7 T1 T2 T3 T4 T5 T6 T7 P1 T1 T2 T3 T4 T5 T6 T7 P2 Extractable Ca (mg/kg) 500 1000 1500 2000 T1 T2 T3 T4 T5 T6 T7 P1 T1 T2 T3 T4 T5 T6 T7 P2 Extractable Mg (mg/kg) 100 200 300 400 T1 T2 T3 T4 T5 T6 T7 P1 T1 T2 T3 T4 T5 T6 T7 P2 Fig.…”
Section: Effects On Soilssupporting
confidence: 81%
“…Soil PR values exceeding 2000 kPa are associated with restricted root growth (Singh and Malhi, 2006). Busscher et al (2010Busscher et al ( , 2011 showed the application of 44 Mg ha -1 of pecan shell-derived biochar (2% dwb) to decrease the PR (measured at θ =10%) of a fine loamy sand from 2.9 to 1.18 MPa. This biochar amendment raised the soil ρ from 1.45 to 1.52 Mg m -3 (Busscher et al, 2010;2011).…”
Section: Introductionmentioning
confidence: 99%
“…Busscher et al (2010Busscher et al ( , 2011 showed the application of 44 Mg ha -1 of pecan shell-derived biochar (2% dwb) to decrease the PR (measured at θ =10%) of a fine loamy sand from 2.9 to 1.18 MPa. This biochar amendment raised the soil ρ from 1.45 to 1.52 Mg m -3 (Busscher et al, 2010;2011). Bekele et al (2015) also showed the PR of a loamy soil to be lowered by a WBC amendment.…”
Section: Introductionmentioning
confidence: 99%
“…When concerning cost of commercial chemical fertilizers as well as human and soil health, locally available organic manure can be used to enhance soil fertility and crop productivity (Hamza and Abd-Elhady, 2010;Mokhtariniya and Siadat, 2011) in developing countries. Addition of organic manures to soil also improves soil physical properties (Busscher et al, 2010) and penetration resistance in loam soils (Alvarez et al, 2009). Moreover, it contains both macro and micro nutrients.…”
Section: Introductionmentioning
confidence: 99%